'For the Lord Will Be Your Confidence … ' Prov. 3:26. Issue 2 (1st September 2021) - Matty, Nazek
Abstract: This short article expresses how one's own experience affects one's reading of the Bible, and how reading the Bible helps the reader to understand their reality differently. Stories that are presented in the Bible are stories in which one can find him/herself. This brief work focuses on what the sages say about shoah and times of crisis. Two verses are considered: Prov. 1:27 and 3:25, where the author gives advice to the reader on how to live wisely in times of distress. Shoah is presented here as a lived experience of the author after being forced to leave their hometown and escape the storm that hit the lives of so many people. Reading the Bible while being a displaced person put us very much in line with the exiled Israelites who lived the experience of loss and shame after 587 BC.